Myeloid zinc finger 1 mediates sulindac sulfide-induced upregulation of death receptor 5 of human colon cancer cells - Horinaka, Mano (Nature Publishing Group, 2014)
A combined therapy of sulindac sulfide and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising strategy for the treatment of cancer. Sulindac sulfide had been shown to induce the expression of death receptor 5 (DR5), a receptor for TRAIL, and sensitize cancer cells to TRAIL-induced apoptosis; however, the molecular mechanism underlying the upregulation of DR5 has not yet been elucidated. We demonstrate here that myeloid zinc finger 1 (MZF1) mediates the induction of DR5 by sulindac sulfide. Sulindac sulfide induced the expression of DR5 at the protein and mRNA levels in colon cancer SW480 cells. Furthermore, sulindac sulfide increased DR5 promoter activity. We showed that sulindac sulfide stimulated DR5 promoter activity via the −301 to −253 region. This region contained a putative MZF1-binding site. Site-directed mutations in the site abrogated the enhancement in DR5 promoter activity by sulindac sulfide. MZF1 directly bound to the putative MZF1-binding site of the DR5 promoter and the binding was increased by sulindac sulfide. The expression of MZF1 was also increased by sulindac sulfide, and MZF1 siRNA attenuated the upregulation of DR5 by sulindac sulfide. These results indicate that sulindac sulfide induces the expression of DR5 by up-regulating MZF1.